Public Trust and Political Forgiveness in Indonesia: A Critical Ethical Analysis Post-2025 National Protests - Rahmat Effendi; Makmur Rizka (JURNAL NAWALA POLITIKA, 2026)
This article examines the ethical paradox underlying the crisis of public trust in Indonesian democracy that followed the 2025 nationwide protests over the housing allowance policy for members of the House of Representatives (DPR). The protests reflected strong moral resistance to injustice amidst socio-economic pressures. Still, the rapid easing of public anger after the policy's revocation suggests a pattern of collective forgiveness that undermines demands for ethical accountability. This Research aims to define forgiveness as a critical ethical category in Indonesian politics. This study utilises a qualitative-descriptive literature review and critical discourse analysis. It combines John Rawls's theory of distributive justice, Alasdair MacIntyre's virtue ethics, and Jürgen Habermas's discourse ethics to interpret the crisis of trust as a question of moral legitimacy rather than simply a policy failure. The analysis demonstrates that forgiveness operates ambivalently: on the one hand, it maintains social harmony and political stability, while on the other, it normalises elite ethical violations. This article proposes a critical ethics of forgiveness as a paradigm for restoring public trust, one that demands reflection, communication, and moral accountability.